A systematic review of associated structural and chromosomal defects in oral clefts: when is prenatal genetic analysis indicated?. Issue 8 (12th August 2012) - Maarse, Wies; Rozendaal, Anna Maria; Pajkrt, Eva; Vermeij-Keers, Christl; Mink van der Molen, Aebele Barber; van den Boogaard, Marie-José Henriëtte
Abstract : Background: Oral clefts—comprising cleft lip (CL), cleft lip with cleft palate (CLP), and cleft palate (CP)—are being diagnosed prenatally more frequently. Consequently, the need for accurate information on the risk of associated anomalies and chromosomal defects to aid in prenatal counselling is rising. This systematic review was conducted to investigate the prenatal and postnatal prevalence of associated anomalies and chromosomal defects related to cleft category, thereby providing a basis for prenatal counselling and prenatal invasive diagnostics. Methods: Online databases were searched for prenatal and postnatal studies on associated anomalies and chromosomal defects in clefts. Data from the literature were complemented with national validated data from the Dutch Oral Cleft Registry. Results: Twenty studies were included: three providing prenatal data, 13 providing postnatal data, and four providing both. Data from prenatal and postnatal studies showed that the prevalence of associated anomalies was lowest in CL (0–20.0% and 7.6–41.4%, respectively). For CLP, higher frequencies were found both prenatally (39.1–66.0%) and postnatally (21.1–61.2%). Although CP was barely detectable by ultrasound, it was the category most frequently associated with accompanying defects in postnatal studies (22.2–78.3%). Chromosomal abnormalities were most frequently seen in association with additional anomalies. In the absence of associated anomalies, chromosomal defects were found prenatally in CLP (3.9%) and postnatally in CL (1.8%, 22q11.2 deletions only), CLP (1.0%) and CP (1.6%). Conclusions: Prenatal counselling regarding prognosis and risk of chromosomal defects should be tailored to cleft category, and more importantly to the presence/absence of associated anomalies. Irrespective of cleft category, clinicians should advise invasive genetic testing if associated anomalies are seen prenatally. In the absence of associated anomalies, prenatal conventional karyotyping is not recommended in CL, although array comparative genomic hybridisation should be considered. In presumed isolated CLP or CP, prenatal invasive testing, preferably by array based methods, is recommended.